2018
DOI: 10.1109/tmm.2017.2780762
|View full text |Cite
|
Sign up to set email alerts
|

Label Distribution-Based Facial Attractiveness Computation by Deep Residual Learning

Abstract: Two challenges lie in the facial attractiveness computation research: the lack of true attractiveness labels (scores), and the lack of an accurate face representation. In order to address the first challenge, this paper recasts facial attractiveness computation as a label distribution learning (LDL) problem rather than a traditional single-label supervised learning task. In this way, the negative influence of the label incomplete problem can be reduced. Inspired by the recent promising work in face recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Additionally, we demonstrate that using our model to select the best dating photos is as accurate as having 10 humans vote on each photo and selecting the best average score. Architecture SCUT-FBP Best Run SCUT-FBP 5 Fold CV HotOrNot MLP [18] 76 71 -AlexNet-1 [42] 90 84 -AlexNet-2 [42] 92 88 -PI-CNN [18] 87 86 -CF [17] 88 --LDL [41] 93 --DRL [25] 93 --MT-CNN [42] 92 90 -CR-Net [22] 87 -48. Through this work, we also conclude that Photofeeler's normalizing and weighting algorithm dramatically decreases noise in the votes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we demonstrate that using our model to select the best dating photos is as accurate as having 10 humans vote on each photo and selecting the best average score. Architecture SCUT-FBP Best Run SCUT-FBP 5 Fold CV HotOrNot MLP [18] 76 71 -AlexNet-1 [42] 90 84 -AlexNet-2 [42] 92 88 -PI-CNN [18] 87 86 -CF [17] 88 --LDL [41] 93 --DRL [25] 93 --MT-CNN [42] 92 90 -CR-Net [22] 87 -48. Through this work, we also conclude that Photofeeler's normalizing and weighting algorithm dramatically decreases noise in the votes.…”
Section: Resultsmentioning
confidence: 99%
“…Anderson et al [24] benchmark a variety of CNN architectures on the CelebA dataset for binary attractiveness prediction. Both Fan et al [41] and Liu et al [25] propose replacing the regression output with a distribution prediction output and using a KL-Divergence loss rather than the standard mean squared error. We adopt a similar architecture to this.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is very important to use another algorithm to improve the detection accuracy. Previously, Fan et al proposed using a deep residual network to enhance the automatic learning of hierarchical aesthetics representation; they found that network performance increased with the number of layers [34,35]. For this reason, we tried adding a layer of fully connected layers that are based on the YOLO network and used the dropout function to prevent overfitting.…”
Section: Algorithm Optimizationmentioning
confidence: 99%
“…The Northeast China database [22], Shanghai database [21], Hot-Or-Not database [32], [33], AVA database [16] and re-sampled face subset of AVA database [34] are large-scale databases involved with FBP, where the Northeast China [22] and Shanghai database [21] are limited for geometric facial beauty analysis without attractiveness ratings; Hot-Or-Not database [32], [33] only focuses on the appearance-based FBP; and the AVA database [16], [34] is originally designed for aesthetic analysis of entire images but not the facial attractiveness. In our previous work, Xie et al [1] published a SCUT-FBP benchmark dataset, which has led to many FBP models [1]- [3], [31], [37], especially the hierarchial CNN-based FBP models with the state-of-the-art deep learning [1]- [3], [37]. Despite the prevalent usage of the SCUT-FBP, it only contains 500 Asian Female faces, which may limit the performance of the datademanded model for FBP.…”
Section: Introductionmentioning
confidence: 99%